Hubungan Pekerjaan, Personal Hygiene, dan Penggunaan Alat Pelindung Diri (APD) terhadap Dermatitis Kontak Iritan di UPT Puskesmas Pagar Merbau Kabupaten Deli Serdang Mei 2026 - Maestro Bina Utama Simanjuntak (Majalah Ilmiah METHODA, 2026)
Background: Dermatitis is an inflammation that occurs on the outer part of the skin, caused by physical interactions or immune system reactions. Contact dermatitis is one type of dermatitis that appears due to substances or materials coming into contact with the skin. Objective: This study aims to analyze the relationship between occupation, personal hygiene, and the use of personal protective equipment (PPE) on irritant contact dermatitis at the Pagar Merbau Community Health Center (UPT Puskesmas) in Deli Serdang Regency. Research Method: This study employed a quantitative design using a cross-sectional approach. The research population included all adult patients aged between 18 and 60 years who attended the UPT Puskesmas Pagar Merbau during the study period. The sample was selected using purposive sampling based on inclusion and exclusion criteria. Data were obtained through a questionnaire that had undergone validity and reliability testing. Data analysis was conducted using a univariate approach to observe frequency distribution and bivariate analysis applying the chi-square test with a significance level of 0.05. Research Results: Univariate analysis showed that the majority of respondents had poor personal hygiene (68.9%), high-risk jobs (55.5%), did not use complete PPE (75.6%), and experienced irritant contact dermatitis (57.8%). Bivariate analysis showed a significant association between personal hygiene and the incidence of irritant contact dermatitis (p-value = 0.044), type of job and irritant contact dermatitis (p-value = 0.000), and PPE use and irritant contact dermatitis (p-value = 0.002). Conclusion: There was a significant association between occupation, personal hygiene, and the use of personal protective equipment (PPE) with irritant contact dermatitis at the Pagar Merbau Community Health Center (UPT), Deli Serdang Regency.